IDENTIFIKASI NEMATODA PARASIT PADA SALURAN PENCERNAAN MARMUT (Cavia cobaya) SEBAGAI SUMBER BELAJAR BIOLOGI PADA MATERI INVERTEBRATA - Septia Nurhasanah; Handoko Santoso (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The research was conducted in the Laboratory of Science Education, University of Muhammadiyah Metro. The research is a descriptive analysis, morphological observations were made by identifying the nematode parasite found that Trichostrongylus sp, Strongyloides sp, Trichuris sp, Trichuris sp. The results showed the prevalence and intensity values is the large number of guinea pigs to parasites divided by the number of guinea pigs that are 100% inspected. While the intensity is seen from the total number of nematode parasites that infect in the number of guinea pigs infected with a parasite that is 2,3. The population in this study was 10 cows pigs (Cavia cobaya ) . This study took a part in the digestion of marmots (Cavia cobaya ) the intestines and stomach , then cut and taken part in the large intestine and be Indian ink or coloring 2-3 drops to be easily identified microscopically . Put the preparations into a petri dish , and given alcohol as much as 96 % with 2-3 drops . Taking part in the examination of the large intestine to taste then used the nematode worm structure with Indian ink dye to be observed , and placed in the glass object . Observed with a microscope. Document if the parasites are found by using the camera Erlina 2008. Identification of the observations made have found 3 types of parasites that attack the guinea pig (Cavia cobaya) is Strongyloides sp on samples 1,2,3,4,5,6 , dan10 . Then parasite Trichuris sp species found in samples 8 and 9. Trichostrongylus sp parasite species found in sample 7 . Parasitic nematodes found were 3 types of Trichostrongylus sp, Strongyloides sp, Trichuris sp. Number of samples that have been observed as many as 10 cows pigs (Cavia cobaya) , with the overall result is as much as 23 tails parasites. Kata kunci: nematode parasit, marmut (Cavia cobaya), sumber belajar biologi.